The Effectiveness Of Government Supervision In Controlling Alcoholic Beverages Based On Merauke Regency Regional Regulation Number 8 Of 2014 - Riez Kifli Kolewora; Rendie Meita Sarie Putri (Punggawa Legacy Center, 2026)
The control of alcoholic beverages constitutes one of the efforts undertaken by local governments to maintain public order and protect society from the adverse impacts arising from the circulation of alcoholic beverages. Although Merauke Regency has enacted Regional Regulation Number 8 of 2014 as the legal basis for regulating and controlling alcoholic beverages, the implementation of its supervisory mechanisms continues to encounter various challenges. This study aims to analyze the effectiveness of government supervision in controlling alcoholic beverages under Merauke Regency Regional Regulation Number 8 of 2014 and to identify the factors influencing its effectiveness. This research employs an empirical legal research method using a socio-legal approach. Data were obtained through literature reviews and documentary studies and were subsequently analyzed qualitatively using descriptive-analytical techniques. The findings indicate that government supervision has not been implemented effectively due to limited institutional capacity, suboptimal inter-agency coordination, low levels of public legal awareness, and inconsistent enforcement of sanctions.The novelty of this research lies in the development of a collaborative supervision model that integrates inter-institutional synergy, community participation, and strengthened legal education as strategic measures to improve the effectiveness of the implementation of Merauke Regency Regional Regulation Number 8 of 2014.